Invasive Epilepsy Monitoring: The Switch from Subdural Electrodes to Stereoelectroencephalography - Coorg, Rohini; Seto, Elaine S. (Journal of Pediatric Epilepsy, 2023)
Stereoelectroencephalography (SEEG) has experienced an explosion in use due to a shifting understanding of epileptic networks and wider application of minimally invasive epilepsy surgery techniques. Both subdural electrode (SDE) monitoring and SEEG serve important roles in defining the epileptogenic zone, limiting functional deficits, and formulating the most effective surgical plan. Strengths of SEEG include the ability to sample difficult to reach, deep structures of the brain without a craniotomy and without disrupting the dura. SEEG is complementary to minimally invasive epilepsy treatment options and may reduce the treatment gap in patients who are hesitant about craniotomy and surgical resection. Understanding the strengths and limitations of SDE monitoring and SEEG allows epileptologists to choose the best modality of invasive monitoring for each patient living with drug-resistant seizures.
Keywords: stereoelectroencephalography; SEEG; subdural electrodes; epilepsy surgery; invasive monitoring; seizure